Red lights: the lives of sex workers in postsocialist China - Zheng, Tiantian (University of Minnesota Press, 2009)
Introduction: Masculinity, power, and the Chinese state -- Patriarchy, prostitution, and masculinity in Dalian -- From banquets to karaoke bars : a new sexual awakening -- Fierce rivalries, unstable bonds : class in the karaoke bars -- Turning the grain : sex and the modern man -- The return of the prodigal daughter -- Clothes make the woman -- Performing love : the commodification of intimacy and romance